(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
This paper presents a research on the pupils conceptual difficulties in the first year of Baccalaureate Experimental Sciences (ES) during the geometrical construction of the virtual image.The experimentation realized in this research takes into account the reality of the teaching in the classroom. It was conducted towards the end of the school year 2012/2013 among a group of learners consisting of 54 pupils. These pupils must only use the traditional method paper, pencil, ruler and protractor for doing tests.By analyzing the conceptual difficulties proven in the false geometrical constructions produced by the pupils, we have marked that the first variant sub-tests do not allow the emergence of the conceptual difficulty associated with the tracing of the construction ray extension. The construction of the virtual image through the second variant sub-tests has shown that about 32 % of pupils face against this conceptual difficulty, which is related to an incorrect status that the pupil attributes to the construction ray extension.After checking the conceptual difficulty related to the correspondence image object (punctual and global) and the conceptual difficulty associated with the minimum number of rays departing from the same point of the luminous object and also the difficulty in tracing a construction ray, it seems that the both variants don’t allow the emergence of these conceptual difficulties.